Development of AKM Class: Analysis Correlation of AKM Value on Students Logical Thinking Skills of 8 Grade Junior High School - Solihin, Nana; Wahidin, Wahidin; Hindriana, Anna Fitri (Journal of Education Reseach and Evaluation, 2023)
The current unresolved problems in education in Indonesia include the weak literacy skills and numeracy skills that occur in students. One way to measure literacy and numeracy skills is through assessment. One form of assessment is through the Minimum Competency Assessment (AKM) which is carried out in class. This study aims to analyze the correlation between AKM classes with logical thinking skills. The research method uses mixed methods. This research was conducted in 3 junior high schools in eighth grade with different geographic locations. There are 60 respondents in total. The data collection technique used by the researcher used a written test in the form of AKM class questions, and for secondary data was an interview. Quantitative data analysis was carried out through prerequisite tests such as validity, reliability, and discriminatory power, level of difficulty, normality test, homogeneity test, and one way ANOVA test. The results of the analysis of the AKM literacy and numeracy AKM scores show that students' reading skills and numeracy skills are categorized as being in the low category. This means that students are still at the level of knowing and understanding. For this reason, it is very important to increase students' reasoning at a higher level in order to realize the implementation of curriculum 2013.